Phytobalneotherapy: When traditional herbal medicine meets spa therapy - Antonelli, Michele; Donelli, Davide (Journal of Medicinal Herbs and Ethnomedicine, 2018)
Phytobalneotherapy (or hay baths) is a balneological treatment which combines the effects of thermal baths and the properties of fermenting herbs. Alpine hay, made of many different herbs harvested in mountain fields, is traditionally used for this treatment. Some studies have investigated the effects of hay baths on health, underscoring their potential benefits for rheumatic conditions. In conclusion, phytobalneotherapy seems an interesting way to harness therapeutic properties of medicinal herbs in a way which appears to be tolerable and sustainable. Further investigation is needed.